Resistência do feijoeiro-comum a quatro raças de Uromyces appendiculatus - FALEIRO, FABIO GELAPE; VINHADELLI, WENDER SANTOS; RAGAGNIN, VILMAR ANTONIO; JR., TRAZILBO JOSÉDE PAULA; MOREIRA, MAURÍLIO ALVES; BARROS, EVERALDO GONÇALVES DE (Revista Ceres, 2015)
.